Inverse and Hyper Zagreb indices: application to quantitative structure properties relationship / Ahmad Nazib Alias ... [et al.] - Alias, Ahmad Nazib; Mohamed Zabidi, Zubainun; Zakaria, Nurul Aimi; Mahmud, Zaidatul Salwa (Universiti Teknologi MARA, Perak, 2021)
The topology index can be derived from molecular connectivity, which can be related to the chemical or physical properties of molecules. The topology indices of alkanes are calculated using the modified-Zagreb index, direct and reciprocal degree distance indices, and the modified-Zagreb index. These indices are tested as the structural descriptor for thermodynamic properties such as boiling point (bp), heat vaporization at 25oC (hv), critical temperature (ct), critical pressure (PC), and magnetooptical properties. Multiple linear regression analyses were done to find the best fitting between these indices and the thermodynamic properties. The results indicate that the boiling point, critical temperature, and heat vapor are reasonably well accounted for by the presence of more than two parameters. The regression equation for the four thermodynamic properties and magnetooptical properties shows a good relation property.